Development of an acquisition system to monitoring asynchronous tele-ultrasound for lung patients - Avilés, E.; Zegarra, C.; Reyes, F.; Castañeda, B.; Romero Gutierrez, S.E. (SPIE, 2023)
Lung ultrasound imaging allows the detection and evaluation of the lung damage generated by COVID-19. However, several infrastructure and logistical limitations prevent them from being carried out in isolated and remote areas. In this work, a system for the acquisition of medical images through asynchronous tele-ultrasounds was developed. The system is based on a graphical user interface, which records the three video cameras, the ultrasound image and the accelerometer simultaneously. The interface was developed according to the Volume Sweep Imaging acquisition protocol. The translational and rotational movement of the transducer are tracked and monitored by the accelerometer and the position of the transducer is obtained from the images acquired by the three video cameras. The results show a correct functioning of the system overall, being viable to be implemented for data acquisition and calculation of error, although in order to validate the error calculation there is still more research to be done.
Keywords: Computer science; Accelerometer; Data acquisition; Interface (matter); Asynchronous communication; Computer vision; Transducer; Ultrasound; Real-time computing; Graphical user interface; Protocol (science); Artificial intelligence; Acoustics; Telecommunications; Medicine; https://purl.org/pe-repo/ocde/ford#1.02.01